PERBEDAAN PENAMBAHAN BERAT BADAN PADA PENGGUNAAN KB SUNTIK 3 BULAN DAN KB SUNTIK 1 BULAN DI WILAYAH KERJA PUSKESMAS DANDER - REZITA ENDRI SUCI RAHAYU, NIM011411231002 (2018)
Background: the most preferred method of contraception is the injection method. There are two types injectable contraception in Indonesia, 3 months injection and 1 month injection. The problem that often arises from the use of both types of contraception is a weight gain. This research aim to analyze the differences of body weight changes in 3 months injection and 1 month injection. Method: This study was conducted analytically observational with cross-sectional approach. With the number of samples is 270 samples. With the following inclusion criteria, using 3-month injection of at least 4 times injection, using a 1 month injection of at least 12 times the injection, body weight before use contraception is known, weight changes recorded on the medical record, registered on the medical record at the health facility. And the exclusion criteria is clients moving from other health facilities, medical records are incomplete. Results: 1 month injection contraceptive user get 62,96% weight gain. While on 3-month injection contraceptive users get 66,66% weight gain. Using Mann Whitney test obtained p value 0.67, which means there is no difference in weight gain of the use of 3 months injection and 1 month injection. Conclusion: there is no difference of weight gain on 3 month injection and 1 month injection in 1 month working area of Puskesmas Dander. Keyword : 3 months injection, 1 month injection, weight gain